Genetic analysis of plant morphology in bambara groundnut (Vigna subterranea (L.) Verdc.) - Ahmad, Nariman Salih (2013)
Bambara groundnut (Vigna subterranea (L.) Verdc.) is an important underutilised legume crop, grown mainly by female subsistence farmers in Africa under traditional low input agricultural systems. Bambara groundnut is known as being of high nutritional value, as an atmospheric nitrogen fixer and to possess high levels of drought, pest and disease tolerance. Bambara groundnut is a predominantly self-pollinated crop and is grown as locally adapted landraces. These are expected to exist as non-identical inbred lines and are generally low yielding. Strategies involving genetic analysis of this species could provide important data for breeding programmes that could enhance food security in Africa. A set of 124 SSR primers designed from different library sources were tested to screen a ‘narrow’ genetic cross (F3) and a ‘wide’ genetic cross (F2) . The former is a cross between domesticated landraces (DipC and Tiga necaru) while the latter is a cross between a domesticated landrace and a wild ancestor (DipC and VSSP11). Residual heterozygosity in the F3 ‘narrow’ cross was confirmed to be around 25% based on 33 polymorphic SSR primers, consistent with an F3 population. A ‘narrow’ cross linkage map was constructed for the first time in bambara groundnut using 269 polymorphic markers (236 DArT and 33 SSR). The map consisted of 238 markers in 21 linkage groups of two or more linked markers, totalling 608.1cM and covering a predicted 54% of the bambara groundnut genome, although the high marker-marker linkage (at 89%) suggests a more comprehensive coverage. QTL analysis was carried out for 73 bulked lines of an F3 population and plants were evaluated for traits in a controlled glasshouse suite and a field trial in Indonesia. Data from single plant analysis of the F2 generation of this cross grown in a controlled environment glasshouse was also used. Most of the QTLs detected were clustered on linkage groups 1, 4 and 12. Major QTLs for internode length and biomass dry weight were detected on LG4 and LG1, respectively, for the FutureCrop glasshouse and field datasets. The highest LOD score of 9.7 was detected for peduncle length and was located within the confidence interval for a QTL for internode length locus. Marker locus bgPabg-596774 was detected to be associated with QTL for six traits; node no./plant, pod no/plant, pod weight, seed no./plant, seed yield and biomass dry weight, on LG1 within one LOD score of confidential interval, potentially suggesting pleiotropic effects of a more limited number (or even one) gene(s). One hundred and fifty-nine additional markers (136 DArT and 23 SSR) were used to improve the existing partial ‘wide’ map (141 AFLP, 1 SSR) constructed in an F2 population of 98 plants. A total of 194 markers were assigned to 20 linkage groups spanning a total of 901 cM. The linkage map derived from the ‘wide’ cross (DipC x VSSP11) had an expected genome coverage of 79.6%. An attempt to combine both maps through 32 common markers allowed a common QTL for days to emergence to be detected in both populations in close association with the common DArT markers 601384 and 601748. The main segregating traits were found to be plant spread, internode length, growth habit, peduncle length, pod weight, seed yield and biomass dry weight. Detecting the same QTL positions for a number of traits, suggested that common underlying genes might be responsible. The QTL-DNA marker associations developed in this study could be used practically for MAS in a future breeding program of this crop.